NEW PHOSPHINATO ORGANO- AND HALOTIN(IV) DERIVATIVES, ADDUCTS AND COMPLEXES: SYNTHESIS AND SPECTROSCOPIC STUDY - BASSENE SEYDOU (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2020)
Five new phosphinato derivatives, adducts and complexes have been synthesized and characterized by infrared and Mössbauer spectroscopies. Based on their spectroscopic data discrete or infinite chain structures are proposed, the phosphinate ion behaving as a bicoordinating bridging or a monocoordinating ligand, the environments around the tin (IV) centers being octahedral or trigonal bipyramidal. In Me4N(SnPh2)2(H2PO2)2Cl3 and Cl2Sn(H2PO2)2NMe4H2PO2, the cation is involved in electrostatic interactions with the anions.